EARLIER DESIGN OPTIMIZATION APLICATION IN THE DESIGN PROCESS OF ROLLER PRESS TYPE OF COAL BRIQUETTING MACHINE - INDRA KOMARA (NIM : 231 06 005); Pembimbing : Dr. Ir. I Wayan Suweca, ASEP
Design is an iterative process. The conventional design process depends on the designerÃ‚Â’s intuition, experience and skill. Nowdays, design is a process to find the optimum solution by using design optimization process. Design is not only the more or the less intuitively guided creation of new information, but also consist of analysis, presentation of results, simulation and optimization. These are essensial constituents of an iterative process leading to feasible and finally optimum design. This earlier design optimization concept will be applied to design roller press system in the coal briquetting machine to find the optimum roller press dimension and briquetting capacity in one single unit machine. The design optimization process of roller press system have a multicriteria objective function with some design parameters which are include coal material properties, briquetting operation condition, and transportation condition. Another parameter connected with geometric modelling will be driven by parametric design. That parameters will be formulated in the mathematic equation and then optimized by using Augmented Lagrange Multiplier (ALM) method. Based on this analysis, It concluded that design optimization by using parametric design in the earlier design of roller press system can be impelemted well. The optimum briquetting capacity is 19,7 tone/hour and the weight of the roller press system is 5268 kg. The value of the design variabel for roller press system can be used as a basic design to the next design step until final detail design development.